Policies and practices of SHEA Research Network hospitals during the COVID-19 pandemic. (23rd October 2020) - Calderwood, Michael S.; Deloney, Valerie M.; Anderson, Deverick J.; Cheng, Vincent Chi-Chung; Gohil, Shruti; Kwon, Jennie H.; Mody, Lona; Monsees, Elizabeth; Vaughn, Valerie M.; Wiemken, Timothy L.; Ziegler, Matthew J.; Lofgren, Eric
Abstract: To understand hospital policies and practices as the COVID-19 pandemic accelerated, the Society for Healthcare Epidemiology of America (SHEA) conducted a survey through the SHEA Research Network (SRN). The survey assessed policies and practices around the optimization of personal protection equipment (PPE), testing, healthcare personnel policies, visitors of COVID-19 patients in relation to procedures, and types of patients. Overall, 69 individual healthcare facilities responded in the United States and internationally, for a 73% response rate.